Development of innovative potential of regions of Ukraine under market transformation - Бєлякова, О. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
The constituents of potential of regional level are investigational, the structure of the national innovative system of Ukraine is presented, the transformation factors of influence are certain, they are given rating description and intercommunication is set with the processes of development of innovative potential